IMPROVING STUDENTS' ABILITY IN COMPREHENDING ENGLISH TEXTS THROUGH PEDAGOGICAL TRANSLATION STRATEGY (AN ACTION RESEARCH TO THE ECONOMICS FACULTY STUDENTS UNIVERSITAS MATARAM) - NAWAWI NAWAWI (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2016)
This study aims at knowing both the process and result of improving students' ability in comprehending English texts through Pedagogical Translation Strategy. The Riel's model of action research method was used to conduct this study. The data was collected through observation, test, interview, questionnaire, and diary. The gained data was analysed statistically or qualitatively in order to know theprocess and the result of improvement caused by the application of Pedagogical Translation Strategy which was eleborated into main instructional actions of first, second and third cyclical Instructional Action Package. It was proved that the quality of process and result of instruction were improved. The average scores for learningprocess increased significantly from 3.1 to 3.4 and to 3.6 in thefirst, second, and third cycle, respectively. Whereas, for learning result, particularly in comprehending English text, students got average scores of 40.2, 59.9, 70.6 and 72.9 in pre-test, cycle I, cycle II and cycle III, consecutively. This means that The pedagogical translation strategy is significantly effective to be used for teaching reading comprehension, particularly English texts. Penelitian ini bertujuan untuk mengetahui proses dan hasil peningkatan kemampuan mahasiswa dalam memahami teks bahasa Inggris melalui Strategi Penerjemahan Pedagogis. Metode penelitian tindakan model Riel digunakan dalam melakukan penelitian ini. Data-data dikumpulkan melalui pengamatan, tes, wawancara, angket, dan catatan harian. Data-data tersebut kemudian dianalisis secara statistik deskriptif atau kualitatif untuk mengetahui proses dan hasil peningkatan yang disebabkan oleh penerapan Strategi Penerjemahan Pedagogis yang dijabarkan menjadi tindakan-tindakan inti dalam Paket Tindakan Pembelajaran siklus pertama, kedua, dan ketiga. Terbukti bahwa kualitas proses dan hasil pembelajaran telah dapat ditingkatkan. Skor rata-rata proses pembelajaran meningkat secara signifikan dari 3,1 pada siklus pertama, menjadi 3,4 pada siklus kedua, dan 3,6 pada siklus ketiga. Selanjutnya, peningkatan hasil pembelajaran ditunjukkan oleh nilai rata-rata tes awal dan siklus pemahaman teks bahasa Inggris. Nilai-nilai tersebut adalah 40,2 pada tes awal, menjadi 59,9 pada siklus pertama, 70,6 pada siklus kedua, dan 72,9 pada siklus ketiga. Hal ini berarti bahwa Strategi Penerjemahan Pedagogis efektif untuk dipergunakan mengajar Pemahaman Bacaan, khususnya teks berbahasa Inggris.